Developing Students' Speaking Ability Through Infographics Media at MAN 4 Bone - Melsiani Melsiani; Nurdevi Bte Abdul; Wildhan Burhanuddin (FKIP Unismuh Makassar, 2023)
The purpose of this study was to determine whether the use of Infographics with MAN 4 Bone students in the tenth grade improved students' speaking skills in terms of fluency, fluency, and vocabulary accuracy. Researchers used a pre-experimental design and quantitative methods using one group for pre and post-tests.In the academic year 2021–2022, 87 students of class X MAN 4 Bone are the population of this study. To select the research sample used cluster random sampling method. The speaking test was used as a data collection method.The results showed that Infographics Media succeeded in improving students' speaking ability. Children's eloquence supports it. The mean pre-test score was 4.82, while the post-test mean score was 7.58. The average pre-test for students' accuracy was 5.10, while the post-test average increased to 7.79. Both the accuracy and fluency value of the t-test were higher than the t-table value (17.82 > 1.701) and the accuracy value of the t-test was higher than the t-table value (16.61 > 1.701). As a result, the Null hypothesis was refuted and the Alternative Hypothesis was adopted. The study researchers came to the conclusion that Infographics media improves students' speaking ability.